KONSELING ISLAMI DENGAN TEKNIK SCALING QUESTION UNTUK MENGURANGI KECEMASAN PASIEN - Khoirun Nisa Dwi Martina; Supandi Supandi (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2017)
This article attempts to describe the process of Islamic counseling with scaling question technique in order to reduce patient's anxiety. The method used is qualitative descriptive, while the determination of the subjects is chosen with the purposive sampling. The results of the study show the practice of scaling question technique with the following sequence of processes: (1) rapport, (2) asking for complaints during hospitalization, (3) asking the patient to take a comfortable position with his eyes closed then feel what the burden of his mind , (4) asking the patient to tell what he is feeling when his eyes are closed, (5) asking the level/problem level between 0 - 10, (6) dialogue plus exposing the wisdom or risk until the patient raises the insight or gets enlightenment, (7) reinforced with the verses of the Qur'an or hadith, (8) asking the level/problem level between 0-10 back, (9) farewell